Approaches to surgical staging of cancer of the uterine cervix - E. G. Bezhanova; I. V. Berlev (Опухоли женской репродуктивной системы, 2017)
Cancer of the uterine cervix is staged using a clinical, rather than a surgical staging system, which is the approach used for other gynecologic tumors. Surgical staging is potentially more accurate. However, the International Federation of Gynecology and Obstetrics (FIGO) has determined that clinical staging is preferable for assessing locally advanced disease (i. e., tumor size, vaginal and parametrial involvement); and it allows to avoid surgery in women who are not candidates for surgical treatment. The staging and pelvic and paraaortic lymph node evaluation for cervical cancer are reviewed here.